2021
DOI: 10.1101/2021.06.09.447812
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recurrent erosion ofCOA1/MITRAC15demonstrates gene dispensability in oxidative phosphorylation

Abstract: Skeletal muscle fibers rely upon either oxidative phosphorylation or glycolytic pathway to achieve muscular contractions that power mechanical movements. Species with energy-intensive adaptive traits that require sudden bursts of energy have a greater dependency on fibers that use the glycolytic pathway. Glycolytic fibers have decreased reliance on OXPHOS and lower mitochondrial content compared to oxidative fibers. Hence, we hypothesized that adaptive gene loss might have occurred within the OXPHOS pathway in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 187 publications
0
1
0
Order By: Relevance
“…It is important to note that SFXN4 is not absolutely required for complex I biogenesis, as some complex I is able to assemble in its absence, and patients with homozygous loss-of-function mutations in SFXN4 are able to live into at least early adolescence ( 7 , 8 ). It will be interesting to determine when SFXN4 emerged as a complex I assembly factor from an evolutionary perspective and whether its role is conserved in some lineages and lost in others, as a recent study demonstrated has occurred for COA1 ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that SFXN4 is not absolutely required for complex I biogenesis, as some complex I is able to assemble in its absence, and patients with homozygous loss-of-function mutations in SFXN4 are able to live into at least early adolescence ( 7 , 8 ). It will be interesting to determine when SFXN4 emerged as a complex I assembly factor from an evolutionary perspective and whether its role is conserved in some lineages and lost in others, as a recent study demonstrated has occurred for COA1 ( 29 ).…”
Section: Discussionmentioning
confidence: 99%